Search for third generation scalar leptoquarks in pp collisions at √s=7 TeV with the ATLAS detector - Aad, G; Abajyan, T; Abbott, B; Abdallah, J; Khalek, SA; Abdelalim, A; Abdinov, O; Aben, R; Abi, B; Abolins, M; Abouzeid, O; Abramowicz, H; et al. (2013)
A search for pair-produced third generation scalar leptoquarks is presented, using proton-proton collisions at s=7 TeV at the LHC. The data were recorded with the ATLAS detector and correspond to an integrated luminosity of 4.7 fb-1. Each leptoquark is assumed to decay to a tau lepton and a b-quark with a branching fraction equal to 100%. No statistically significant excess above the Standard Model expectation is observed. Third generation leptoquarks are therefore excluded at 95% confidence level for masses less than 534GeV. [Figure not available: see fulltext.] © 2013 Cern for the benefit of the ATLAS collaboration.